Computational Analysis of Subcooled Flow Boiling in a Vertical Minichannel with Two Different Shapes under Various Mass Fluxes - A. Igaadi; H. El Mghari; R. El Amraoui (Journal of Applied Fluid Mechanics, 2023)
In the current research project, two-dimensional numerical simulations are conducted to analyze the effects of geometrical configuration on flow structures and the thermal performances of subcooled flow boiling. The CFD simulations are carried out in two different configurations (straight and periodic constriction expansion) in a minichannel mounted vertically at four mass fluxes (500 kg/m2s; 836.64 kg/m2s; 1170 kg/m2s; and 2535 kg/m2s). The present predicted results exhibit excellent accordance with the previous experiments, with mean errors of 6.39% and 9.78%, demonstrating the efficiency of the present numerical study. The simulation results show that the periodic constriction expansion design provides good mixing between the layers, leading to a 43.11% mean enhancement of the thermal transfer, which is more important than the slight pressure drop penalty of 4.32 for a mass flux of 500 kg/m2s due to the combined pressure drop along the minichannel that resulted from the periodic constriction and expansion regions. Furthermore, the visualization of flow patterns shows that the bubbly flow is the dominant flow regime in the periodic constriction-expansion configuration.